2002
DOI: 10.1080/01926230252824699
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Liver Cell Function and Proliferation: Differentiation Between Adaptation and Toxicity

Abstract: Exposure of experimental animals to biologically effective levels of chemicals, either endogenou s or exogenous , the latter of either synthetic or natural origin, elicits a response(s) that re ects the diverse ways in which the various units of organization of an organism deal with chemical perturbation. For some chemicals, an initial response constitutes an adaptive effect that maintains homeostasis. Disruption of this equilibrium at any level of organization leads to an adverse effect, or toxicity. The live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 99 publications
(117 reference statements)
4
90
0
7
Order By: Relevance
“…In addition, the liver weight of the birds exposed to lindane increased significantly. The liver somatic index LSI went from 1.7 (controls) to 2.9 (lindane injected birds); the difference could be attributed to the impact of the insecticide as a consequence of the liver enlargement secondary to exposure to the insecticide due to compensatory proliferation processes (Williams and Iatropoulos, 2002).…”
Section: Gland Physiologymentioning
confidence: 99%
“…In addition, the liver weight of the birds exposed to lindane increased significantly. The liver somatic index LSI went from 1.7 (controls) to 2.9 (lindane injected birds); the difference could be attributed to the impact of the insecticide as a consequence of the liver enlargement secondary to exposure to the insecticide due to compensatory proliferation processes (Williams and Iatropoulos, 2002).…”
Section: Gland Physiologymentioning
confidence: 99%
“…RXRα plays a crucial role in the ligand-dependent transactivation of various genes involved in drug and lipid metabolism by forming a heterodimeric complex with numerous members of the NR superfamily, including retinoic acid receptor (RAR), vitamin D receptor (VDR), thyroid hormone receptor, pregnane X receptor (PXR), constitutive androstane receptor, peroxisome proliferator-activated receptor (PPAR), farnesoid X receptor, and liver X receptor. It has been demonstrated that more than 300 genes in humans can be transactivated by RXRα [1].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the distinction between metabolomics and metabonomics is not always clear, and, as is common, these terms will be used interchangeably within this text. Regardless of terminology, the comprehensive analysis of metabolites in biological systems is an important aspect of studies that are aimed toward further understanding complex processes such as those associated with aging and development [6,7], disease [8], drug efficacy [9], and xenobiotic toxicity [10,11]. Metabolomics is viewed as holding great promise, for example, in specific biomarker discovery for clinical diagnostics, drug discovery, and development.…”
mentioning
confidence: 99%